FDPP–HA as a theranostic agent for cancer-targeted fluorescence imaging and photodynamic therapy. Issue 59 (27th July 2017) - Liang, Pingping; Shao, Jinjun; Tang, Qianyun; Si, Weili; Wang, Qiang; Zhang, Qi; Dong, Xiaochen
Abstract : FDPP–HA was synthesized for tumor targeting photodynamic therapy. All experiments reveal that FDPP–HA presents excellent biocompatibility, high phototoxicity and specific targeted fluorescence imaging properties. Abstract : In clinics, for photodynamic therapy (PDT) it is challenging to achieve photosensitizers with properties of high singlet oxygen quantum yield, tumor targeting and fluorescence imaging simultaneously. Herein, a furan flanked diketopyrrolopyrrole (FDPP) molecule, with good singlet oxygen quantum yield (∼26%), is covalently connected to hyaluronic acid (HA) to obtain a water-soluble photosensitizer (FDPP–HA), which presents good specific targeting to HCT-116 tumor cells both in vitro and in vivo . FDPP–HA also exhibits excellent biocompatibility, low dark toxicity and high phototoxicity, which can effectively inhibit the tumor growth in vivo by PDT. The design of FDPP–HA in this work provides a general strategy for cancer target-specific fluorescence imaging and PDT.